A clinicopathological aspect of primary small-cell carcinoma of the uterine cervix: a single-centre study of 25 cases. Issue 12 (30th September 2011) - Li, Jun-Dong; Zhuang, Yuan; Li, Yan-Fang; Feng, Yan-Ling; Hou, Jin-Hui; Chen, Liang; Zhu, An-Na; Wu, Qiu-liang; Yun, Jing-Ping
Abstract : Aims: Small-cell carcinoma is a variant of poorly differentiated neuroendocrine carcinoma. Primary small-cell carcinoma of the cervix (SCCC) is recognised as a rare and aggressive malignant tumour with poor prognosis. In this study, the authors report 25 Chinese cases of SCCC, with a particular focus on their clinical and pathological characteristics. Material and methods: The records of 25 patients from 4075 Chinese patients with cervical cancer were collected and reviewed, including the patients' age, initial symptoms, cervical tumour size, International Federation of Gynaecology and Obstetrics clinical stage, lymph-node metastasis, treatments and follow-up results. Immunohistochemical detection was performed for cytokeratin, epithelial membrane antigen, neuron-specific enolase (NSE), synaptophysin (Syn), chromogranin A (CgA), neuronal cell adhesion molecules (CD56), thyroid transcriptional factor-1 and S100 protein (S100). Results: The median age of 25 patients with SCCC was 43.7 years. The most common symptom was abnormal vaginal bleeding. Histologically, there were 19 'homogenous' SCCC samples and six samples of SCCC mixed with adenocarcinoma. The proportion of SCCC samples with positive immunoreactivity were 100.0% for NSE, 96.0% for Syn, 68.0% for CD56, 76.0% for CgA, 40.0% for thyroid transcriptional factor-1, 84.0% for epithelial membrane antigen, 68.0% for cytokeratin and 8.0% for S100, respectively. Every patient received one to three types of treatments, including surgery, chemotherapy and radiotherapy. The median survival time of patients was 20.9 months after diagnosis. Conclusion: The higher proportion of positive labelling of Syn, CD56, CgA, and NSE in SCCC implicated that they are valuably applied in a differential diagnosis of the malignancy. The patients with SCCC receive one to three types of therapies, including surgery, chemotherapy and radiotherapy, and have a poor prognosis.